(untitled) (Journal of Hama University, 2024)
Wild mustard, Brassica nigra, is one of the most common flowering herbs associated with wheat and barley crops in Syria. Since its flowers may be a source of food for adults of the genus Collryia (Hymenoptera: Ichneumonidae), which is one of the most important parasitoids of the wheat stem sawfly (Hymenoptera: Cephidae), which are harmful to wheat and barley crops, this research therefore aimed to study the effect of the availability of this herb on the edges of its fields. In increasing the efficiency of these parasites with the aim of improving the process of biological control of the wheat stem sawfly, as well as the vitality of the wheat stem sawfly because they are always observed gathering on its flowers. Experiments were conducted in the fields of the Soran area in Hama Governorate by planting a variety sensitive to wheat stem sawfly infestation (Sham 5) in the form of two treatments with or without wild mustard. The results showed an increase in the efficiency of the parasite Collyria spp. When wild mustard was available; The average parasitism rate on sawfly wasp eggs was recorded at 27.4%, compared to 18.78% when wheat was grown alone, with significant differences between them, which indicates the presence of a positive effect of the wild mustard herb in increasing the parasitism rates with these parasites. However, on the other hand, the presence of the herb Mustard had a negative effect, represented by an increase in the rate of infection of wheat plants with wheat stem sawfly. The average field infection rate reached 25.6% in the presence of wild mustard, while the infection rate was 14.1% when wheat was grown alone, with significant differences between them. The life span and fertility of female wasps also increased with Feeding on wild mustard flowers compared to females that were not presented with flowers. Accordingly, we suggest the necessity of getting rid of this weed within the field and its edges, and at the same time searching for other sources of flowering plants that can be planted on the edges of the fields or as strips within the fields during the period of the presence of wheat stem sawfly so that they are only supportive of the parasitoids.